Duodenal morphometry in COBB 500 chickens supplemented with essential oil of oregano (Origanum vulgare L) - Campozano-Marcillo, Gustavo Adolfo (2021)
The aim of this study was to evaluate the effect of the addition of oregano essential oils (OEO) in the diet on duodenal morphometry of Cobb 500 broilers. In total, 400 chickens distributed in five treatments were used: supplementation with OEO (100, 200, 300 ppm) and two control treatments (commercial oregano [250 ppm] and growth-promoting antibiotic [300 ppm]), for six weeks, fed ad libitum with weekly formulated diets. The morphometric study was carried out with the help of a camera coupled to the microscope using AmScope 3.0 software, a 4x objective, covering an area of 2000 µm2. The variable proximal width of the villi was significantly greater (183 µm) in the OEO 300 ppm treatment at 21 days of age and the variable proximal depth was significantly greater (256 µm) in the OEO 300 ppm treatment at 42 days (p<0.05). It is concluded that the addition of OEO in doses of 300 ppm positively affect the duodenal morphometry of Cobb 500 chickens.